Aggression during early childhood: Associated factors in a clinical sample [Erken çocukluk döneminde agresyon: Klinik bir örneklemde i̇lişkili faktörler] - (:unkn) unknown (My University, 2011)
Objective: Early onset aggression is a public health problem. We aimed to investigate the associated factors of aggressive behaviours in preschool children. Patients and Methods: Seventy two children (aged between 1 and 6) with primary complaints of severe aggressive behaviours by their parents and 72 healthy controls were included in the study. A semi-structured inquiry-form on demographic features, personal and psychiatric characteristics of parents and mother-child relationship patterns were given to the mothers. The Aberrant Behaviour Checklist (ABC) and Beck Depression Inventory (BDI) were given to the mothers. Results: Parental education levels were lower in the patient group. Parents' problematic experiences with anger, mothers' feelings of insufficiency in parenting and marital quarreling were found to be higher in the patient group. The frequency of depressive and/or anxiety symptoms during pregnancy and the postnatal period as well as mothers' current BDI scores were higher in the patient group. According to a logistic regression analysis, the ABC hyperactivity score, mothers' feelings of insufficiency in parenting and fathers' problematic experiences with anger were found to be associated with aggressive behaviours in the patients. Conclusion: Aggression in preschool children is associated with multiple factors. The examination of parental characteristics appears to be especially important in the evaluation of affected children. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Aggression; Children; Preschool age